Fabry disease in Argentina: an evaluation of patients enrolled in the Fabry Registry. Issue 1 (13th December 2012) - Politei, J. M.; Cabrera, G.; Amartino, H.; Valdez, R.; Masllorens, F.; Ripeau, D.; Antongiovanni, N.; Soliani, A.; Luna, P.; Cedrolla, M.; Fernandez, S.; Fainboim, A.
Summary Aims: Fabry disease (FD) is an X‐linked inborn error of metabolism caused by alpha‐galactosidase A deficiency. The Fabry Registry is an ongoing, global observational database that compiles clinical data from patients with FD. Methods: Demographic and baseline clinical characteristics of Fabry Registry patients enrolled in Argentina were analysed and compared with patients enrolled in the rest of the world (ROW). Baseline clinical parameters included chronic kidney disease (CKD) stage, urine protein‐to‐creatinine ratio and left ventricular posterior wall thickness. Only data from untreated patients were included. Results: As of 1 October 2010, 3752 patients were enrolled in the Registry, 70 patients from Argentina and 3682 from the ROW. Argentinean male subjects were younger than Fabry Registry male subjects enrolled in ROW: mean current age 32.5 years vs. 39.0 years for men (p = 0.0257 by t‐test). The current age (mean ± standard deviation) of female subjects enrolled in Argentina was not significantly different from that of female subjects enrolled in the ROW: 40.1 ± 17.28 vs. 43.2 ±17.95 years respectively (p = 0.2967). Overall, a smaller percentage of patients from Argentina received ERT compared with patients in the ROW (54% vs. 58% respectively). When evaluated by gender, more men and fewer women in Argentina received ERT compared with ROW (85% vs. 79% for men and 27% vs. 38% for women). A larger proportion of patients in ROW had severe CKD (stage 4 or 5) compared with Argentina (9.8% vs. 0%), most likely because of the older age of the ROW population. Conclusions: The enrolment of Argentinean patients into the Fabry Registry has steadily increased, as has the inclusion of female and paediatric patients with FD. The medical community in Argentina should be aware of FD in these populations, as awareness will facilitate prompt diagnosis and initiation of treatment, thus leading to improved outcomes.